Detailed analysis of adenosine A2a receptor (ADORA2A) and CD73 (5′-nucleotidase, ecto, NT5E) methylation and gene expression in head and neck squamous cell carcinoma patients. (3rd August 2018) - Vogt, Timo J.; Gevensleben, Heidrun; Dietrich, Jörn; Kristiansen, Glen; Bootz, Friedrich; Landsberg, Jennifer; Goltz, Diane; Dietrich, Dimo
Abstract: Background : The adenosine A2a receptor (A2aR) and the adenosine synthesizing enzyme CD73 have recently evolved as a novel immunotherapeutic target. However, little is known about epigenetic modification of the encoding genes ADORA2A and NT5E . Methods : In the present study, we evaluated methylation at 23 loci of ADORA2A and 17 loci of NT5E with regard to transcriptional activity, human papilloma virus (HPV) status, immune cell infiltration, and outcome in a cohort of 279 head and neck squamous carcinoma (HNSCC) patients obtained from The Cancer Genome Atlas (TCGA). Methylation and mRNA expression were generated by the Infinium HumanMethylation450 BeadChip and Illumina HiSeq 2000 RNA Sequencing Version 2 analysis (Illumina, Inc., San Diego, CA, USA). HPV status was assessed by RNA-Seq data analysis of the viral genes E6 and E7. Results : Thirteen out of 23 ADORA2A loci and 15/17 NT5E loci were significantly correlated with mRNA levels ( p  < 0.05). Inverse correlations were predominately found in promoter regions, while positive correlations were more profound at intragenic loci. ADORA2A hypermethylation was significantly associated with poor overall survival (OS, p  ≤ 0.030), whereas NT5E hypomethylation was associated with decreased OS in HPV-positive tumors ( p  ≤ 0.024) and increased OS in HPV-negative HNSCC ( p  ≤ 0.029). Further, we found significant correlations between methylation and immune cell infiltrates. Conclusion : Our data might point towards a significant role of the A2aR/CD73 axis during cancer progression in HNSCC.